Achieving conservation impact by shifting focus from human attitudes to behaviors. Issue 1 (12th August 2019) - Nilsson, Danielle; Fielding, Kelly; Dean, Angela J.
Abstract: Attitudes have been a commonly used psychological measure of program effectiveness in conservation social science research. The major limitation of this approach is that attitudes do not always translate into behavior and therefore may not provide an accurate assessment of program success. Given that achieving conservation goals generally relies on understanding and changing human behavior, we argue for the need to assess behavior rather than attitudes as an indicator of conservation outcomes. Psychological theory shows that attitudes and behavior are distinct, but related, concepts. Measuring conservation behaviors involves identifying the target behavior or behaviors and the optimal time to measure and then selecting the most appropriate method of measurement (i.e., direct observation, objective indicators, self‐reported behavior, and behavioral intentions) that considers the strengths and weaknesses of each approach. We call for conservation programs to focus on influencing behavior rather than attitudes alone and encourage conservation practitioners and researchers to collect high‐quality behavioral data to more effectively inform policy and programs. Abstract : Article impact statement : Encouraging researchers and practitioners to collect behavioral data and promote behavior change improves policy and program outcomes. Abstract : Logro del Impacto de la Conservación Cambiando el Enfoque en las Actitudes Humanas a los Comportamientos Resumen: Las actitudes han sido utilizadas comúnmente como una medida psicológica de la eficacia de una investigación de ciencias sociales de la conservación. La principal limitación de este enfoque es que las actitudes no siempre se traducen en comportamiento y, por lo tanto, pueden no proporcionar una evaluación precisa del éxito del programa. Dado que el logro de los objetivos de conservación generalmente se basa en la comprensión y el cambio del comportamiento humano, argumentamos la necesidad de evaluar el comportamiento en lugar de las actitudes como un indicador de los resultados de conservación. La teoría psicológica muestra que las actitudes y el comportamiento son conceptos distintos, pero relacionados. La medida de comportamientos de conservación implica la identificación del comportamiento o los comportamientos buscados y del tiempo óptimo para medirlos y luego seleccionar el método de medición más apropiado (i. e., observación directa, indicadores objetivos, comportamiento auto reportado e intenciones de comportamiento) que considere las fortaleza y debilidades de cada enfoque. Hacemos un llamado para que los programas de conservación se centren en influir en el comportamiento en lugar de las actitudes por sí solas y alentamos a que los profesionales e investigadores de la conservación recopilen datos conductuales de calidad para que las políticas y programas tengan información eficaz. 摘要: 在保护的社会科学研究中, 常常用态度作为评估项目有效性的心理指标。这种方法主要的局限性在于态度并不总能转化为行动, 因此可能无法准确评估项目成效。鉴于实现保护目标通常有赖于理解和改变人类行为, 我们认为需要把行为评估作为一项保护成效的指标, 而非态度。心理学理论表明, 态度和行为是不同的, 但又是相互关联的概念。对保护行为的测量包括确定目标行为和最佳测量时间, 并考虑每种测量方法的优缺点以选择最合适的测量方法 (即直接观察、客观指标、自我报告的行为, 以及行为意向) 。我们呼吁保护项目应重点关注影响行为的转变而不仅是态度, 并鼓励保护实践者和研究者收集高质量的行为数据, 从而更好地为政策和保护项目提供信息。【翻译: 胡怡思; 审校: 聂永刚】